Impact of the Internal Marketing Control in the Quantity of Banking Services in the International Islamic Arab Bank - Falah Al-Zoubi & Nayla Diab, Ali (British Journal of Marketing Studies, 2017)
This study aimed at investigating the nature of relationship between the five elements of the internal marketing control (control evidence, information systems, process of evaluating risks, control activities, and control techniques follow up) and among dimensions of service quality (substantial elements, dependable (validity), haste of response, security, concern “sympathy” in the International Islamic Arab Bank. To achieve objectives of this study, a sample of directors, responsible of control, and heads of departments in the International Islamic Arab Bank through its headquarters, and its branches stretched all over the areas of the Jordan, and those who work in this domain. The sample amounted to (150) individuals. Hypothesis of study were tested through using Pearson Correlation Coefficient, and the multi and simple linear regression. From the most important results which had been deduced that there is a significant statistical relationship between the elements of internal marketing represented in the environment of control, information and communications systems, risks analyzing, systems of control, procedures of following up and supervision and among the dimensions of service quality. Based on those results, numerous recommendations have been deduced, of them: in order to guarantee the quality of work, banks have to enhance procedures of the internal marketing control depending on the modern approaches in evaluating these procedures through analyzing the risks connected with them. The significance of this approach appears with the increase of using technology to cover all activities of the bank.